Sensitive, Highly Multiplexed Sequencing of Microhaplotypes From the Plasmodium falciparum Heterozygome. (25th August 2020) - Tessema, Sofonias K; Hathaway, Nicholas J; Teyssier, Noam B; Murphy, Maxwell; Chen, Anna; Aydemir, Ozkan; Duarte, Elias M; Simone, Wilson; Colborn, James; Saute, Francisco; Crawford, Emily; Aide, Pedro; et al.
Abstract: Background: Targeted next-generation sequencing offers the potential for consistent, deep coverage of information-rich genomic regions to characterize polyclonal Plasmodium falciparum infections. However, methods to identify and sequence these genomic regions are currently limited. Methods: A bioinformatic pipeline and multiplex methods were developed to identify and simultaneously sequence 100 targets and applied to dried blood spot (DBS) controls and field isolates from Mozambique. For comparison, whole-genome sequencing data were generated for the same controls. Results: Using publicly available genomes, 4465 high-diversity genomic regions suited for targeted sequencing were identified, representing the P. falciparum heterozygome. For this study, 93 microhaplotypes with high diversity (median expected heterozygosity = 0.7) were selected along with 7 drug resistance loci. The sequencing method achieved very high coverage (median 99%), specificity (99.8%), and sensitivity (90% for haplotypes with 5% within sample frequency in dried blood spots with 100 parasites/µL). In silico analyses revealed that microhaplotypes provided much higher resolution to discriminate related from unrelated polyclonal infections than biallelic single-nucleotide polymorphism barcodes. Conclusions: The bioinformatic and laboratory methods outlined here provide a flexible tool for efficient, low-cost, high-throughput interrogation of the P. falciparum genome, and can be tailored to simultaneously address multiple questions of interest in various epidemiological settings. Abstract : A novel bioinformatics pipeline was created to select and characterize the most diverse and tractable short-range sequences (microhaplotypes) in the Plasmodium falciparum genome, followed by a robust polymerase chain reaction–based multiplexing method to simultaneously amplify and sequence these microhaplotypes.